The Effect of Ethanol Extract 96% o Brown Rice Bran to the Number and Viability of White Rat (Rattus norvegicus) Spermatozoa Sprague dawley Strains Induced by Clove Cigarette Smoke - Soraya Rahmanisa; Natasya Hayatillah; Evi Kurniawaty (Berkala Kedokteran, 2018)
Abstract: Indonesia has the greatest number of smokers in Southeast Asia dominated by male consume kretek cigarette. Cigarette’s smoke is source of free radicals that can cause oxidative stress to sperm and lead it to infertility. Red rice bran extract has lot of potential antioxidants to stop oxidatif stress. This study was experimental within 30 days. The 25 Sprague dawley male rats divided into 5 groups: K1 wasn’t treated, K2,P1,P2, and P3 exposed to smokes of 2 kretek cigarettes, given 96% ethanol extract of red rice bran dosage 100 mg/Kg (P1), 200 mg/Kg (P2) and 400 mg/Kg (P3). Spermatozoa number and viability was observed. Data tested with One Way Anova. There was significant effect from red rice bran extract toward sperm number and viability (p=0,00). Average spermatozoa number was 91.90±7.72 (K1), 39.68±7,51 (K2), 79.88±8.63 (P1), 86.40±10.5 (P2), 86.00±5.78 (P3). Average viability was  65.00±6.85 (K1), 29.6±5.85 (K2), 51.4±3.50 (P1), 60.00±6.67 (P2), 61,00±2.91 (P3). The increasing of number and viability has been achived at dose 100mg/Kg and best at 400 mg/KgBB. The 96% ethanol extract of  red rice bran can prevent the decreasing number and viability of rat spermatozoa exposed by kretek cigarette. Keywords: Clove cigarette, spermatozoa, rice bran extract